Large bowel obstruction secondary to gallstones. Issue 5 (18th May 2021) - Crosen, Matelin; Ghattas, Paul; Sandhu, Rovinder
Abstract: Gallstone ileus is a rare complication of cholelithiasis, representing 1% of bowel obstructions. The usual site of obstruction is the ileocecal valve, though other sites have been reported. Here, we present two cases of gallstone ileus within the distal colon requiring surgical intervention. Two elderly females presented with vague abdominal symptoms secondary to large bowel obstruction from gallstone impaction. Both underwent attempted endoscopic retrieval without success. Patient 1 required laparoscopy converted to exploratory laparotomy with colotomy and removal of the stone. Patient 2 required partial colectomy and end colostomy formation due to acute sigmoid inflammation. Gallstone ileus is a rare cause of intestinal obstruction, though incidence increases with age. Cholecystocolonic fistulas allow stones to bypass the ileocecal valve, with the potential for impaction in the colon at the site of a stricture or tortuosity. Surgical intervention may be required in cases not amenable to successful endoscopic retrieval.